Pengaruh bimbingan kelompok client centered tentang pendidikan seks islami terhadap perilaku (meliputi pengetahuan, sikap dan tindakan) pencegahan penyimpangan seksual pada remaja awal perempuan - Anin Wijayanti (NHM PRESS, 2018)
Sexual deviation is also called as abnormalor deviant sexual behaviors tending to sexualcrimes. The increasing deviation for the past threeyears in Mojokerto and its proximity is LGBT(lesbian, gay, bisexual and transsexual), it occuredon teenagers aged from 14 years. Children andteenagers approaching adolescence are actuallygroups with a risk of having sexual deviation, butthey often do not realize it. Thus, they need moreconcern from parents and teachers. The researchaimed to analyze the influence of client centeredgroup coaching approach regarding islamic sexeducation toward the prevention of sexual deviationbehaviors on preadolescence female teenagers atSDIT Permata Kota Mojokerto. The type of theresearch is quasi-experimental design, by using nonrandomized pre test-post test control-group design.The research was conducted from February to June2015, with a population of 97 teenagers and asample of 30 which were taken by using stratifiedrandom sampling. In order to analyze the behaviorsof case group and control group before and aftergroup coaching, the test used Independent SamplesTest and the result suggests that t count (4.881 and16.529) is greater than t table (1.993), with a significance value 0.000 (<0.05). In order to knowthe influence of group coaching to behavioral change the researcher used Paired SamplesCorrelations and the result suggests that t count (10.048) is smaller than t table (2.045), with asignificance value of 0.000 (<0.05). Conclusion: teenagers' behaviors before andafter group coaching can be categorized as positive,and there were effects of group coaching toward theincrease of preventing behaviors. It is suggested thatthe school keeps conducting weekly coaching groupwith the most effective methods to satisfy the needsod teenagers and prioritizes the use of Islamiccontents materials (religious approach).